Do clic na EJA ao furo da lata: experimentações fotográficas na educação e no cotidiano - RODRIGUES JUNIOR, Walter Gomes (Universidade Federal do Pará, 2017)
This study reveals two processes of experimentation with the image through photography: the first aimed at a group of students of Youth and Adults (EJA) from a Public School in Bethlehem / PA, and the second directed at a group of young community of the District of Mainland on the outskirts of Bethlehem / PA. Seeking to unleash new subjectivities and interpretations from experimenting with photography in its many aspects, we point our lenses as well as a production technique, in the direction of a perception that step into what we see those who build their own identity. The whole process experienced was concerned to develop the aesthetic sense of students and especially in re-educate the eye to a more sensitive, attentive to detail the day-to-day and critical, based on principles of observation, experimentation and research. We chose this approach because we believe that photography, all given end trajectory imagery, historical and conceptual, within and outside a school context, can contribute to the training of individuals in society.